Effects of wheat protein on the formation and structural properties of starch-lipid complexes in real noodles incorporated with fatty acids of varying chain lengths. (June 2021) - Kang, Xuemin; Sui, Jie; Qiu, Hongwei; Sun, Chunrui; Zhang, Huayong; Cui, Bo; Abd El-Aty, A.M.
Abstract: In this study, the effect of proteins (10%, w/w ) on the formation of starch-lipid complexes (measured by Rapid Visco Analyzer (RVA)) in pure starch and noodles supplemented with different fatty acids (such as, lauric acid (LA), glycerol monolaurate (GML), stearic acid (SA), and glycerol monostearate (GMS), 3% w/w ), in addition to their impacts on in vitro enzymatic digestion were assessed. The addition of protein and lipids increased the viscoelastic properties of wheat starch (WS) samples. The V-type diffraction intensity of WS-lipid sample mixed with protein was increased compared to WS-lipid samples without protein. Noodles enriched with fatty acids (particularly LA) showed higher relative crystallinity and enzyme resistant starch (ERS) compared to noodles without fatty acid incorporation. As shown by microscopic computed tomography (mCT), the crystalline pattern of noodles supplemented with LA and GML displayed a higher density than those incorporated with SA and GMS; the findings which are in line with thermal resistance and X-ray diffraction analysis. In sum, this study could foster a better understanding of the interplay between biomolecules during processing. Graphical abstract: Image 1 Highlights: Proteins promoted the formation of starch-lipid complexes. Starch-lipid inclusion complexes was formed in noodles. The starch-lipid complexes lowered the in vitro enzymatic digestibility of noodles. The differences in crystalline of noodle and WS sample are proved by XRD and microCT.